Gobernanza energética y gobernanza ambiental: Dilemas del desarrollo en la integración suramericana - Gisele Lorena González Celis (Atlantic Review of Economics (ARoEc), 2018)
– The development model proposed for the economies of the world is based on a vision that includes economic growth. This idea is supported by the use of natural resources to provide the raw materials required for the system. However, from the concern for the consequences in the environment -by inadequate extractive practices, little or not controlled- government actions have had to regulate economic activities. However, public policies related to the environment have not been so forceful, to the point that when an environmental policy is faced with an energy, the latter prevails over the other. The vision of development has evolved from the hand of many authors who suggest a fundamental change in the conception of it. Despite this, the predominant economic system continues to hold on to the classic idea of the extraction of natural resources. Colombia is a sample of it. Its environmental regulatory framework is broad and contains important instruments for environmental regulation, has a national biodiversity policy, as well as a system of protected areas, has incentives for corporate environmental responsibility and promotes sustainable development and energy efficiency in companies. Despite this, the country's economic model continues to base its production system on the exportation of raw materials, agricultural products and the extraction of hydrocarbons, precious stones and minerals. It should be noted that in Latin American legislation mechanisms are established so that activities, for example extractive activities, comply with environmental protection requirements, however these are not fully met. What is missing from environmental policies to guarantee environmental governance that is linked to energy governance? Based on this response, the elements that are required to identify the type of development we want as a society in the integration process as UNASUR can emerge. Therefore, this analysis is carried out, using the symbolic cartography of Boaventura De Soussa Santos, on three maps that will later overlap. The first corresponds to establish the differences between the environmental and the energetic in a chronological way for the understanding of their incompatibility. In the next one, governance is studied as a way that, by its constitution, may facilitate the articulation between the environmental and the energetic, since it includes several actors in decision-making. The interaction between the different actors requires a clarification between what is involved in sustainability and sustainable development, a topic addressed in the third moment. The result of the overlap is the need to reconstruct the concept of sustainable development, because the differences between the approaches and the amplitude of it makes that between the environmental and the energetic deepen the incompatibility, instead of minimizing it.
Keywords: Q01; Q28; Q56; R58; 330; Environmental governance; energy governance; public policies; development; regional integration